2020
DOI: 10.3389/fphys.2020.605145
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Sugar Is Required for Sex Pheromone Biosynthesis in Mythimna separata

Abstract: Supplemental nutrients of adult moths maximize moth fitness and contribute to the pollination of many plants. Previous reports have revealed that sugar feeding promotes to sex pheromone biosynthesis by increasing the haemolymph trehalose concentration in mating moths. Here, Mythimna separata adults were employed as a model to investigate the effect of sugar feeding on sex pheromone biosynthesis. Results showed that in virgin females, sugar feeding markedly increased the concentrations of trehalose, pyruvic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 44 publications
(71 reference statements)
3
12
0
Order By: Relevance
“…In the present study, we also found that sugar feeding increased the mRNA expression of PYK transcript and PYK activity, consistent with previous results (Krones et al, 2001;Kaloyianni et al, 2004), which indicated the conserved activation of PYK. These results were also consistent with the finding that the supplemental nutrition of female moth promoted the increase of trehalose, pyruvic acid, and acetyl-CoA levels in PGs, and the increase of sex pheromone production in H. armigera, M. separata, and H. virescens (Foster, 2009;Zhang et al, 2020), which elucidated the importance of the role of PYK in sex pheromone biosynthesis. Our results also demonstrated that PBAN treatment did not influence the mRNA level expression of the HaPYK transcript.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the present study, we also found that sugar feeding increased the mRNA expression of PYK transcript and PYK activity, consistent with previous results (Krones et al, 2001;Kaloyianni et al, 2004), which indicated the conserved activation of PYK. These results were also consistent with the finding that the supplemental nutrition of female moth promoted the increase of trehalose, pyruvic acid, and acetyl-CoA levels in PGs, and the increase of sex pheromone production in H. armigera, M. separata, and H. virescens (Foster, 2009;Zhang et al, 2020), which elucidated the importance of the role of PYK in sex pheromone biosynthesis. Our results also demonstrated that PBAN treatment did not influence the mRNA level expression of the HaPYK transcript.…”
Section: Discussionsupporting
confidence: 90%
“…These results were in agreement with finding obtained for H. virescens, where the absence of sugar feeding decreased hemolymph trehalose concentration and the levels of acetyl-CoA, which finally decreased sex pheromone production (Foster, 2009). Similar results were also found in female M. separata, in which blocking of the sugar intake led to a decrease of glycolysis efficiency, as shown by the decrease in the concentrations of trehalose, pyruvic acid, and acetyl-CoA in the PGs, which finally resulting in the significant decrease of sex pheromone titer and subsequent mating efficiency (Zhang et al, 2020). These results were also consistent with the process of sex pheromone biosynthesis.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations